Instant Payment Systems Research: A Bibliometric Study - Loso Judijanto (Westscience Press, 2026)
This bibliometric study analyzes the evolution and current state of research on Instant Payment Systems (IPS). By utilizing citation analysis, co-authorship network analysis, and keyword co-occurrence mapping, the study identifies the key trends, influential authors, and emerging topics in IPS research. Blockchain technology is highlighted as the central theme, reflecting its growing role in enabling secure, efficient, and decentralized payment systems. The analysis also reveals the increasing prominence of electronic money, digital payments, and mobile payment solutions in IPS studies. A global collaboration network emerges, with contributions from both developed and emerging economies, indicating the widespread interest and adoption of IPS technologies. The study uncovers gaps in the literature, particularly in areas such as cross-border payment solutions, regulatory frameworks, and security concerns, which remain critical for the future development of IPS. This paper offers valuable insights for researchers, policymakers, and practitioners looking to understand the trajectory of IPS and identify opportunities for further innovation and collaboration.